HUBUNGAN ANTARA DUKUNGAN SUAMI DAN KELUARGA DENGAN PEMBERIAN ASI EKSKLUSIF PADA IBU PEKERJA SEKTOR FORMAL (Studi pada Wilayah Kerja Puskesmas Kebakkramat I) - Alya Hanifa Lisma Febita; Syamsulhuda Budi Musthofa; Novia Handayani (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Exclusive breastfeeding for babies will reduce the risk of developing infectious diseases. Many women in Kebakkramat sub-districts work in the formal sector because this area is industrial. Working mothers who are breastfeeding need to divide their time between babysitting and their work, so they need support from their husbands and families to achieve exclusive breastfeeding. This research aimed to analyze the relationship between husband and family support with the exclusive breastfeeding behavior in the work area of Kebakkramat I Health Center. This study conducted using quantitative observational study methods with a cross-sectional approach. The population in this research was 113 of formal sector worker mothers who had babies aged 6-12 months. The sample in this study was 55 respondents selected using simple random sampling. The results of this study showed that the majority of respondents already have good support from their husbands and families, but as many as 80% of husbands who have not suggested respondents to participate Ojek ASI program and 70.9% of families suggest giving complementary foods of breastmilk to babies under 6 months. There is a significant relationship between husband support (p-value= 0,000) and family support (p-value= 0.029) with exclusive breastfeeding behavior. Health workers need to provide correct information about exclusive breastfeeding to husbands and families so they can provide positive support for breastfeeding mothers.